2020
DOI: 10.1111/jgs.16321
|View full text |Cite
|
Sign up to set email alerts
|

Aging, Diabetes, Obesity, and Cognitive Decline: A Population‐Based Study

Abstract: BACKGROUND/OBJECTIVES: To investigate potential mechanisms underlying the well-established relationship of diabetes and obesity with cognitive decline, among older adults participating in a population-based study. DESIGN/SETTING: Ten-year population-based cohort study. PARTICIPANTS: A total of 478 individuals aged 65 years and older. MEASUREMENTS: We assayed fasting blood for markers of glycemia (glucose and hemoglobin A1c [HbA1c]), insulin resistance (IR) (insulin and homeostatic model assessment of IR), obes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(27 citation statements)
references
References 38 publications
1
26
0
Order By: Relevance
“…In our study, no associations between HbA 1c levels and changes in cognitive function were observed in participants without diabetes (data not shown). Nevertheless, when HbA 1c was measured as a continuous variable, we found negative associations between high baseline values in HbA 1c levels and all the cognitive tests measured, except in the case of the CDT and the DSTs, thus aligning with findings from recent studies (34,36).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In our study, no associations between HbA 1c levels and changes in cognitive function were observed in participants without diabetes (data not shown). Nevertheless, when HbA 1c was measured as a continuous variable, we found negative associations between high baseline values in HbA 1c levels and all the cognitive tests measured, except in the case of the CDT and the DSTs, thus aligning with findings from recent studies (34,36).…”
Section: Discussionsupporting
confidence: 90%
“…Longitudinal studies linking insulin resistance, as measured by HOMA-IR, and cognitive decline have shown discrepancies. In an older U.S. population with 8 years of follow-up, baseline HOMA-IR was not associated with changes in global cognitive function (36). However, in surviving patients with coronary heart disease, baseline HOMA-IR was associated with subsequent poorer cognitive performance on the composite cognitive score over 15 years (37).…”
Section: Discussionmentioning
confidence: 85%
“…In such analyses, attrition is not treated as missing completely at random or non-informative; instead, covariates are used to model attrition and incorporate this into the main model of cognitive impairment or incident dementia (joint modeling) or take the method that has taken informative dropout into model specification (competing risks modeling). Other approaches via propensity score modeling (Dorsett, 2010;Ganguli et al, 2015;Wolinsky et al, 2010) and inverse probability weighting (Daza et al, 2017;Ganguli et al, 2020) can be used to reform the original dataset via matching or weighting in accordance with non-response or attrition bias, thus allowing results to be generalized back to the original cohort. We caution that these post-hoc methods only help to minimize attrition bias and do not "magically" repair serious biases in the data.…”
Section: Discussionmentioning
confidence: 99%
“…Marden, Mayeda ( 45 ) reported that each percentage point increase in HbA1c was associated with a 0.052 unit decrease on a custom memory score per decade even in individuals without clinical diabetes. In a population-based cohort study HbA1c of 6.2% or greater predicted faster cognitive decline in individuals aged between 65 and 88 even after adjusting for age, sex, education, and APOE ε4 status ( 46 ). A cross-sectional study of patients with T2D showed a non-linear association between HbA1c levels and cognitive function that indicated a bell-shaped relationship with low and high HbA1c levels affecting cognitive decline ( 47 ).…”
Section: Type II Diabetesmentioning
confidence: 99%